Interest Rate Pass-Through in Nepal - Maskay, Nephil Matangi; Pandit, Rajendra (NRB Economic Review, 2010)
The paper examines the interest rate pass through of the policy interest rate to the market interest rate in Nepal. The span of the empirical exercise covers the phase of interest rate liberalization commencing from the first quarter of 1989/1990 to the final quarter of 2008/2009. The result suggests that there is a significant long run elasticity coefficient of the policy rate (taken to be the bank rate) to the different market rates (e.g. 1 yr fixed deposit, lending rate and saving rate), but there is only one error correcting relationship between the bank rate and the lending rate in the short run. However, the speed of adjustment, i.e. the adaptation coefficient, indicates a weaker adjustment of the short-term dynamics to the long run equilibrium. Looking at the sub-sample, which coincides with the promulgation of the NRB Act 2002, the period starting from the third quarter of 2001/2002 to the final quarter of 2008/2009, suggests that there is insignificant elasticity coefficient between the policy rate and two of the above-mentioned market rates. Paradoxically, while the elasticity coefficient between the policy rate and lending rate is found to be significant, it is negative! Overall, the situation indicates that at present, the bank rate in Nepal is ineffective in influencing the market rates and suggests that there are other factors at play. The paper ends by recommending introduction of a more effective indicator of monetary stance, greater awareness of external factors when making monetary policy, and enhancing and guiding the development of the domestic financial sector for equitable financial development and growth.